Pengaruh Background Pendidikan Ekonomi dan Diversitas Gender terhadap Tingkat Utang pada Perusahaan Sub Sektor Bank yang Terdaftar di Bursa Efek Indonesia - Reval Ahmad Khaibar; Budi Safatul Anam; Hendri Mauliansyah (AKUNTANSI 45, 2025)
This study aims to analyze the effect of economic education background and gender diversity of the board of directors and commissioners on the level of debt in bank sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the 2021-2023 period. The background of this research is based on the increasing attention to Environmental, Social, and Governance (ESG) principles, as well as the important role of company board characteristics in financial decision making, especially in terms of capital structure. This research uses a quantitative approach with panel data regression analysis techniques and Common Effect Model (CEM), Fixed Effect Model (FEM), and Random Effect Model (REM) estimation models. Data is obtained from the company’s audited annual financial statements, as well as information on the profiles of directors and commissioners from 12 companies during the observation period. The results of the analysis show that simultaneously, economic education background and gender diversity affect the level of debt. Partially, gender diversity has a significant effect on debt levels, and economic education background has a significant effect on debt levels. These findings indicate the importance of female representation in the leadership structure of companies in shaping more conservative and risk management-oriented financial policies.